2015
DOI: 10.4103/0976-237x.166828
|View full text |Cite
|
Sign up to set email alerts
|

Benign fibrous histiocytoma: A rare case involving jaw bone

Abstract: Benign fibrous histiocytoma (BFH) is a soft tissue neoplasm which occurs mostly on the skin of extremities. BFH rarely occurs in bone and may affect femur, tibia, and pelvic bone. Jaw bone involvement is very unusual with only 11 cases reported till date. This report describes a case of BFH occurring in a 30-year-old female patient affecting left mandibular posterior region. Computed tomography revealed a well-defined expansile lytic lesion in the posterior mandible. Gross examination of the tumor revealed an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…BFH has a tendency to recur [13,26,27]. BFH of the jaws is unusual, can be painful and demonstrates progressive expansion of the posterior mandible [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…BFH has a tendency to recur [13,26,27]. BFH of the jaws is unusual, can be painful and demonstrates progressive expansion of the posterior mandible [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, the foam cells are usually seen in small focal clusters and the dominant microscopic appearance is of a spindle cell proliferation arranged in whorls and storiform fascicles [14][15][16]. Thick collagen band entrapment and multinucleated giant cells are almost always seen [14][15][16]. Hemorrhage and hemosiderin pigment may also be found [14].…”
Section: Discussionmentioning
confidence: 99%
“…Jaw lesions may or may not be painful but show progressive expansion of the posterior mandible including the angle and ramus area [15,16]. Histopathologically, the foam cells are usually seen in small focal clusters and the dominant microscopic appearance is of a spindle cell proliferation arranged in whorls and storiform fascicles [14][15][16]. Thick collagen band entrapment and multinucleated giant cells are almost always seen [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most bony BFHs occur in the pelvic bone, femur and tibia, which share identical histological characteristics with cutaneous BFH (5)(6)(7)(8). However, mandibular involvement of BFH is rare and only 11 cases have been reported to date (5,7,(9)(10)(11)(12)(13)(14)(15)(16). The present study reported a case of mandibular multiple BFH treated at the Affiliated Hospital of Stomatology, Sun Yat-Sen University (Guangzhou, China), who was followed up for 46 months.…”
Section: Introductionmentioning
confidence: 72%